Análisis de contenido del Diario “La Prensa” Digital y su red social Facebook sobre la representación de los migrantes establecidos en la ciudad de Riobamba, periodo 2019-2020 - Pacheco Alcocer, Verónica Johanna (2024)
ABSTRACT: The main objective of this research study focus on analyzing the content of the digital newspaper "La Prensa" and its social network on Facebook on the migratory representation in the city of Riobamba in the period 2019-2020, arising in response to the need to know the information management of this media through its digital tools. The results are presented as follows: In Chapter I, there is an introduction to the topic, along with its referential framework, problem statement, justification and research objectives; in Chapter II, the theoretical framework of the research is developed based on terms of communication, digital communication, Functionalist Theory, journalistic genres, journalism, content analysis, printed media in Ecuador and in the city of Riobamba, migration and social representation; Chapter III presents the methodology, design, population, sample, techniques and instruments applied in the research; in Chapter IV, the research results are analyzed through content matrices and complemented with interviews to experts on the subject; and finally in Chapter V, the results of the research work are obtained, with their respective recommendations.